Dihydromyricetin Inhibits Ferroptosis to Attenuate Cisplatin-Induced Muscle Atrophy - You, L (Physiological research, 2024)
Cisplatin is a widely used chemotherapy drug for the treatment of various cancers. However, although cisplatin is effective in targeting cancer cells, it has severe side effects including skeletal muscle atrophy. In this study, we aimed to characterize the role of Dihydromyricetin in cisplatin-induced muscle atrophy in mice. 5-week-old male C57BL/6 mice were treated with Dihydromyricetin for 14 days orally followed by in intraperitoneally cisplatin administration for 6 days. Gastrocnemius muscles were isolated for the following experiments. Antioxidative stress were determined by peroxidative product malondialdehyde (MDA) and antioxidants superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities. Quadriceps muscle mass and grip strength were significantly restored by Dihydromyricetin in a dose-dependent manner. Moreover, muscle fibers were improved in Dihydromyricetin treated group. Excessive skeletal muscle E3 ubiquitin-protein ligases in cisplatin group were significantly repressed by Dihydromyricetin treatment. Dihydromyricetin significantly reduced oxidative stress induced by cisplatin by decreasing MDA level and restored SOD and GPx activities. In addition, ferroptosis was significantly reduced by Dihydromyricetin characterized by reduced iron level and ferritin heavy chain 1 and improved Gpx4 level. The present study demonstrated that Dihydromyricetin attenuated cisplatin-induced muscle atrophy by reducing skeletal muscle E3 ubiquitin-protein ligases, oxidative stress, and ferroptosis.
Keywords: Oxidative Stress; svalová atrofie; Ferroptosis; cisplatina; flavonoly; Antioxidants; Muscular Atrophy; oxidační stres; Muscle, Skeletal; Cisplatin; myši inbrední C57BL; zvířata; Animals; Male; myši; Antineoplastic Agents; mužské pohlaví; antioxidancia; Mice; ferroptóza; kosterní svaly; protinádorové látky; Flavonols; Mice, Inbred C57BL